Lessons of synaesthesia for consciousness: Learning from the exception, rather than the general. (29th July 2016) - Deroy, Ophelia; Spence, Charles
Abstract: The question of whether the mechanisms underlying synaesthesia are similar to those ones underlying widespread cases of multisensory interactions tends to overshadow the question of whether their manifestations can be thought of as being continuous with one another. Here we focus on the conscious manifestations of synaesthesia and crossmodal correspondences and consider the dimensions along which these could be organised on a continuum. While synaesthesia and crossmodal correspondences may differ regarding the degree of vividness, frequency, specificity of the conscious manifestation, and control over its content, we demonstrate that these dimensions fail to lead to the expected continuous distribution. We suggest that the traditional distinction between conscious and non-conscious conditions might not be sufficient to separate synaesthesia from crossmodal correspondences, but highlight that the conscious manifestations that characterize synaesthesia remain exceptional and cannot be reconciled with other occasional occurrences of crossmodal mental imagery documented in the case of crossmodal correspondences. Highlights: Synaesthesia and crossmodal correspondences can both have conscious manifestations. The oft mentioned difference comes from the frequency of conscious manifestations. Differences also exist regarding vividness, specificity and control. These dimensions do not lead to a continuous distribution. Synaesthetic concurrents present a distinctive cluster of characters.